Effects of Coaches’ Personality, Behavior, Approach and Role on Players Performance with the Mediating Role of Coaches’ Training Method - Chen, Shiqiang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Objective: The current research work is proposed to explore the impact of coaches’ psychological elements on their training and players' performance. Additionally, the current research work also determines the mediation role of training methods between these psychological elements of coaches and players' performance. Method: A quantitative research approach was adopted to obtain the results of the current research work. Hence a survey of 370 football players, was conducted aimed to collect primary data from the football players in China. Then Partial Least Square (PLS) was used to analyze the primary data. Results: It is obvious from the results of the current research work that psychological elements of coaches such as their personality, behavior, approach, and role directly impact their training method and players' performance. It is also evident from the current research that training methods also play a vital role in players' performances. Implications: The current research work provides a boost for greater understanding between the relationship of coaches’ personality, behavior, approach, training method, and players' performance. Furthermore, this research work helps players, coaching staff, and authorities in the sports industry to enhance players' performance.